Fine in the criminal legislation of foreign countries (Journal of actual problems of jurisprudence, 2019)
In this article, the author examines the views of the fi ne features of a form of criminal punishment in other countries, the authormakes an analysis of statistics and the problems arising from the application of the penalty.Keywords: punishment, imprisonment, criminal fi nes, penalties, imprisonment, the magistrate, the defendant, exposing criminalfact.